Heavy metals in private car dust collected from Universiti Malaysia Pahang, Gambang Campus: Contamination and human health risks - Tay, Joo Hui; Nurhameeza, Zakaria (Penerbit Universiti Malaysia Pahang, 2021)
A pilot study was conducted to investigate the concentrations of seven heavy metals (Zn, Cu, Cr, Cd, Fe, Ni and Pb) in private car dusts collected from Universiti Malaysia Pahang (UMP), Gambang campus. Ten private cars were selected among UMP staffs and students, and the dust samples were obtained by using a conventional vacuum cleaner with a clean nylon sampling sock pre-inserted into the suction nozzle. All samples were acid-digested with aqua regia solution and analysed for metal concentration using Atomic Absorption Spectrometry (AAS). The highest mean concentrations were recorded for Fe (650± 480 mg/kg), followed by Zn (160 ± 110 mg/kg), Cu (76.2 ± 18.5 mg/kg), Pb (39.2 ± 99.1 mg/kg), Ni (6.39 ± 8.30 mg/kg), Cr (3.42 ± 5.90 mg/kg) and Cd (0.55 ± 1.40 mg/kg). Hazard quotient (HQ) and hazard index (HI) values lower than 1 indicated no potential non-carcinogenic risks to the adult drivers.